PsyCap Training: Increasing the Psychological Capital of Company X Employees in Facing the Era of Disruption - Suryani, Indri; Hakim, Gamma Rahmita Ureka (Universitas Negeri Malang, 2024)
Psychological capital is a psychological construct encompassing self-efficacy, optimism, hope, and resilience, which are core factors that contribute to the emergence of positive organizational behavior (POB) or measurable, developable, and channelable positive behavior in an organization. Developing psychological resources becomes crucial for facing challenges and changes during an era of IT industry disruption. This research examines the effectiveness of a PsyCap training program in increasing the psychological capital of Company X employees in facing the disruption era. The quantitative research method with a quasi-experimental research design was used to measure changes in values during the intervention (pretest-posttest). A purposive sampling technique was used to select 60 subjects based on their level of psychological capital characteristics. The PsyCap training program was designed based on Luthans’ theoretical framework, utilizing treatment instruments in the form of a PsyCap training module. Data analysis involves two types of analysis: descriptive analysis and parametric statistical analysis using the paired sample t-test. The research findings reveal a comparison of the level of psychological capital between experimental and control groups, with a gain score value of .001 (less than .05) and a sufficient level of effectiveness (66 percent). The results of this research suggest that PsyCap training treatment on an experimental group of employees at Company X is effective for enhancing psychological capital. As a suggestion for future researchers, it is recommended that they be more cautious in controlling the presence of extraneous variables.